Patient Characteristics and Preferences Regarding Anticoagulant Treatment in Venous Thromboembolic Disease - Lanéelle, Damien; Le Brun, Charles; Mauger, Chadi; Guillaumat, Jérôme; Le Pabic, Estelle; Omarjee, Loukman; Mahé, Guillaume; , SFMV VTE Study Group (Frontiers in Cardiovascular Medicine, 2021)
Background: Anticoagulants are the recommended treatment for venous thromboembolic disease (VTE). The mode of anticoagulant administration may influence compliance, and therefore the effectiveness of the treatment. Unlike in atrial fibrillation or cancer-associated thrombosis, there is only limited data on patient preferences regarding the choice of anticoagulation in VTE. This study aims to evaluate patient preferences regarding anticoagulants in terms of administration: types (oral or injectable treatment) and number of doses or injections per day. Patients and Methods: This is a national survey through a questionnaire sent by e-mail to 1936 French vascular physicians between February and April 2019. They recorded the responses for each patient admitted for VTE. Results: Three hundred and eleven (response rate of 16%) of the 1936 contacted physicians responded for 364 patients. Among these, there were 167 fully completed questionnaires. Most patients (63%) express concerns about VTE and prefer oral treatment (82%), justified by the ease of administration (77%) and a fear of the injections (23%). When patients were taking more than three oral treatments they statistically chose injectable treatment more often (57%) than oral treatment (25%, p=0.002). Patients who chose injectable treatment were also older (70±16 versus 58 ±17 years old, p=0.001). There was no statistically difference in anticoagulation preference according to gender or to the expected duration of treatment (6 weeks, 3 months, 6 months or unlimited).When oral treatment was preferred (81%), most chose oral treatment without dose adjustment and biomonitoring (73%). Among them, very few (7%) preferred a twice-daily intake. Conclusion: Patient preference in terms of anticoagulant treatment in VTE disease is in favor of oral treatment without adjustment or biomonitoring and with once-daily intake. When an injectable treatment is chosen, a prolonged duration of treatment does not seem to be a constraint for the patient.